A SYNTACTICAL ANALYSIS OF PHRASES USED IN SONG LYRICS OF DREAM BY BABYMONSTER - Ari Fajria Novari; Rizdki Elang Gumelar; Ghafera Kamelia Zahrotuhayaty (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2024)
This research is about a syntactical analysis of phrases in song lyrics of Dream by Babymonster wuth using Bottom-up tree diagram by Carnie. This research aims to analyze the type and the sum of phrases used in Dream by Babymonster song lyrics. This research used a qualitative approach with a qualitative descriptive method. The data collection technique in this research involved observation, documentation, and checklists. The finding showed that data had all types of phrases based on theory of Carnie, such as noun phrase, verb phrase, adjective phrase, adverb phrase, and prepositional phrase. All phrases found amounted to 150. Those are 65 noun phrases, 51 verb phrases, 16 adverb phrases, 11 prepositional phrases, and 7 adjective phrases. This research can be a contribution in teaching materials, particularly those related to phrases in Syntax subject.